Comparison of the crack opening displacement determination algorithms for a cohesive crack - Selivanov, M.F.; Chornoivan, Yu.O. (Reports of the National Academy of Sciences of Ukraine, 2017)
Two algorithms are given to determine the cohesive crack opening. These algorithms take into account the singularity of the crack opening derivative at the crack tips. The first algorithm is based on the condition of crack closing smoothness. The second algorithm is an iterative, method whose implementation leads to a linear system for the displacement densities at collocation points on each step. This algorithm is more effective for some combinations of the problem parameters because of the approximate determination of the cohesive zone length.